An android and web based application ‘Urban Healthcare Service’ to improve the health care system of bangladesh - Islam, Shah Md. Monirul; Khan, Faria Hoque; Swaqeeb, Md. Najmus (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.